Pemakaian Bahasa dalam Komunitas Mobile Legend: Studi Etnografi Virtual Sosiolinguistik - Nirwana, Nirwana; Iffah Muthmainnah; Saribunga, Sisilia; Candra Dewi, Anita (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstrak: From a sociolinguistic standpoint, this study investigates language use in the Mobile Legend virtual game community. The study analyzes how language serves as a medium for social cohesiveness, identity formation, and norm establishment in digital environments using a virtual ethnography technique. Participant observation and content analysis of interactions within Mobile Legend community platforms were used to gather data. The results show a number of unique patterns of language use, such as game-related specialized registers, linguistic variances impacted by players' sociocultural backgrounds, and language functions that promote unity and govern social standards. The study shows that language has a vital role in forming community identity and preserving social harmony in virtual gaming communities, in addition to being a medium for communication. In the quickly changing digital age, this study advances our knowledge of language dynamics in virtual communities and applies sociolinguistic theories to virtual settings.